â€œPRODUCTS POSITIONING OF MEN FACIAL WASH BASED ON ATTRIBUTES PRODUCT USING MULTIDIMENSIONAL SCALING ANALYSIS (MDS)â€ (Study at Menâ€™s Student Faculty of Economic and Business University of Brawijaya) - Firmansyah, Dimas Bagus (Jurnal Ilmiah Mahasiswa FEB, 2014)
The aim of this research is to describe product positioning map of facial wash for men based on attributes product. This research focus to see the product variance, quality, design, futures, brand name, packaging, sizes, services, warranties, returns of each facial wash for men. The population in this research is a student Faculty of Economic and Business University of Brawijaya which customers of product MensBiore/Nivea For Men/Vaseline Men/Lâ€™Oreal Men Expert/Garnier Men/Gatsby Face Wash, or OXY. This research sample is 100 people. The sampling method utilized in this research is non probability sampling. Research instrument was tested using factor and reliability test analysis. To find out the product positions using Multidimensional Scaling Analysis (MDS) in software SPSS for Windows 16.0.The results showedGarnierMendominatealmostallthe attributes ofproduct perceptions, andMensBioreoneproductattribute. And attributes product of OXY alwaysbeat thelowest levelthan seven productsoffacial wash for men. Keywords: Brand Positioning, Attributes Product, Facial Wash, MDS